PENGARUH UMUR POHON, POSISI BATANG, TEBAL VENIR DAN KOMPOSISI PANEL INTI SAWIT TERHADAP PRODUKSI KAYU LAPIS MINDI - Jamal Balfas; Jamaludin Malik (Jurnal Penelitian Hasil Hutan, 2020)
This study examined the effect of tree age, trunk position, veneer thickness, and composition of panel core of oilpalm wood on mindi plywood production. Oil palm logs of 1.3 m length were cut from two sources of trees with differentages, i.e. 25 and 32 years old. Four logs were collected from the bottom toward the top of each tree in which ten trees fromrespective age classes were selected randomly and cut into logs. Logs from each age class were peeled in spindleless rotarymachine respectively into two thickness of veneer, i.e. 2.5 and 3.4 mm. Dried veneers (MC 10%) were assembled intotwo kinds of panel, i.e. 3 and 5 plies, where the face and back layer were made using 1.2 mm veneer of mindi (Meliaazedarach) wood. Results showed that trunks from the 32 year old tree have higher green and dry veneer recoveriesthan those of the 25 year old tree. Moisture content and density of the 25 year old panels core are lower than thosemade from the 32 year old veneer. Bonding strength of panels made from the 32 year old core veneer is higher than thatmade from the 25 year old veneer. The 3 layer panels have higher bond strength than those of the 5 layer panel. Panelsmade from 2.5 mm core veneers have lower bonding strength than those made from 3.4 mm veneers.